Communication Policy: the Efforts to Strengthen Civil Society - Ratmanto, Teguh (FIkom Unisba, 2008)
In the last decades there were a tendency to make public institution more open and greater public participation in decision making. It is believed that transparency is the only way to strengthen public institutions which it is highly possible because of the progress in Information and Communication Technology. Nowadays Indonesia is entering the Era of Opennes. The idea of civil society and establisihng social welfare which is the first priority require partnership between the government and public. The whole stakeholder should cooperate to improve accessibility on ICT and should develope information and communication infra structure, and should improve application of ICT in every aspect of public services.